An Extensive Orofacial Vascular Malformation - A Case Report - K S Ganapathy; S Latha; Satish Yalamanchili (Wolters Kluwer Medknow Publications, 2005)
Vascular lesions of the head and neck are common. Confusing terminology, lack of knowledge regarding lesion behavior and poorly understood diagnostic criteria often leads to improper diagnosis. Proper history, clinical examination and investigations help us to arrive at a correct diagnosis, which can considerably influence the treatment and its outcome. A case report with clinical and imaging findings of an extensive vascular malformation and treatment options for such vascular lesions is discussed.